Behavioral Patterns Towards Ozone Therapy for Hepatitis C Infection (Ozone Therapy Global Journal, 2019)
During the last decade, Viral Hepatitis C (HCV) has emerged as a new biological threat. Studies were performed in Egypt, between 1999 and 2008 to evaluate the role of ozone therapy for HCV. Whether the disease was in early or late stage, ozone therapy was found to be an effective, safe and, less expensive method in treating hepatitis “C” patients, used alone or in combination with drug therapy. Our study aims to investigate attitudes among physicians and patients towards the disease conditions, predisposing factors and, different therapeutic approaches including ozone therapy for HCV.  Using two interview questionnaires, first for physicians (n=42) and the second for patients (n=50), managing HCV cases, via face to face structured interviews at the site of treatment reception in Cairo and Alexandria. Sites were grouped into three categories: (1) Ministry of Health governmental organizations and university hospitals (2) Army Facilities (3) Private clinics and centers. Snowball sampling method for ozone therapy, and conventional therapists interviewed after obtaining permission from the director of each establishment visited.  Negative attitudes towards ozone therapy were observed among our study sample physicians with significant differences when distributed by place of study and physician’s specialty.  In our study sample 38.1% of physicians believe that ozone therapy is not scientific evidence-based medicine. Moreover, 54.8% assumed that ozone is an illegal and unapproved therapy for HCV.  (93.1%) of the patients interviewed in governmental organization clinics and university hospitals never received ozone.  62.5% interviewed in private and army clinics had ozone therapy, and they all had positive attitudes towards ozone therapy for HCV. More research is needed to elucidate the debate concerning ozone therapies.